PENGARUH BIAYA OPERASIONAL DAN VOLUME PENJUALAN TERHADAP LABA BERSIH PADA PT. CYBERINDO MEDIA UTAMA KABUPATEN KARAWANG - Mira Anggraeni; Cicie Prilianti (Jurnal Riset Multidisiplin Edukasi, 2025)
The background of this research is based on the phenomenon of inconsistent net profit fluctuations, despite the company showing year-over-year increases in sales volume. The discrepancy between revenue increases and net profit stability indicates potential inefficiencies in the company's cost structure and operational strategy. This study aims to analyze the effect of operating costs and sales volume on net profit at PT. Cyberindo Media Utama, Karawang Regency, from 2020 to 2024. The theory in this study relates to Operating Costs, Sales Volume, and Net Profit. The research method used is a quantitative method with an associative approach. The data source is secondary data obtained from PT. Cyberindo Media Utama in time series format, with a total of 52 samples taken using a purposive sampling technique. Data collection techniques include observation, documentation, and literature review. The main estimation models in panel data regression used in this study are the Common Effect Model (CEM), the Fixed Effect Model (FEM), and the Random Effect Model (REM). Three types of tests were used to determine the panel regression model: the Chow test, the Hausman test, and the Lagrange Multiplier test. Data analysis techniques included classical assumption testing and hypothesis testing using statistical calculations using Eviews version 12. The results of the study, using the Fixed Effects Model (FEM), indicate that operating costs have a positive and significant partial effect on net profit. This means that increased operating costs allocated efficiently to support operational activities and sales can actually increase company profits. Meanwhile, sales volume did not significantly affect net profit partially, indicating that increased sales may not necessarily be accompanied by increased profits due to possible additional costs or operational inefficiencies. However, simultaneously, operating costs and sales volume significantly influenced net profit